Atypical Microglandular Hyperplasia of Endocervix as the Presenting Feature of Plasminogen Deficiency. (May 2021) - Stewart, Colin J.R.
Abstract : A 30-yr-old patient with no significant past medical history presented with postcoital bleeding and was found to have fibrinous pseudomembranous lesions overlying and partly in continuity with the endocervical mucosa. Histologically, these were characterized by an atypical microglandular proliferation that was associated with extensive fibrinous exudate and a prominent neutrophil polymorph infiltrate. Ligneous stromal alteration was not identified but the changes prompted hematologic review which confirmed plasminogen deficiency. A subsequent endometrial biopsy also demonstrated degenerate glands within a fibrin-rich matrix. This is the third case demonstrating an association between atypical endocervical microglandular hyperplasia and plasminogen deficiency. The diagnosis should also be considered when biopsies demonstrate exuberant fibrin exudate even if ligneous disease is not present.